Feminine Identity and Education through Literature: Critical Analysis on Coeducational Collections for Children and Young People - Pena Presas, Montse (Madrygal. Revista de Estudios Gallegos, 2015)
During the last few years, the Galician literature system has witnessed the appearance of many different coeducation collections for children and young people that were promoted by institutional initiatives. The aim of this article is to contextualize them –revealing their precedents– as well as analysing them from a literature education point of view and from the perspective of the different feminine identities included in these collections.
Keywords: Coeducation collection; literature education; feminism; feminine identity; children’s literature